MSME’S Perception to Accounting Conceptual: Case Study in Batam - Alfonsa Dian Sumarna; Doni Putra Utama (Universitas Pamulang, 2022)
To fulfil the needs of Micro, Small, and Medium Enterprises (MSMEs) is an important major. The SAK EMKM 2018 is made simpler than the previous issued SAK ETAP. The SAK EMKM was issued to encourage and provide the facilities for MSMEs in preparing the financial statement. The financial statement is one of the requirements for applying for credit to the relevant agencies. This study used the quota sampling method with the minimum sample which is calculated by using Slovin formula for as many as 115 respondents. The questionnaires use the semantic differential scale. The result of this research is that 80% of the respondents have never attended the SAK EMKM training and socialization. And only 34,78% of the respondents have done simple bookkeeping to record their business transactions, even though they have not applied the SAK EMKM. The factors that cause MSME do not do the bookkeeping are the lack of knowledge about the correct accounting based on the right standard and the consideration of being wasting time. Overall, the perception of MSMEs towards the understanding about the SAK EMKM is still in the “Don’t Understand” category. And most respondents as 58.49% expect regular accounting training according to applicable standards (which are simple ones) for business owners.